Construction of heterostructured g-C3N4@TiATA/Pt composites for efficacious photocatalytic hydrogen evolution. (20th September 2019) - Gao, Ziqian; Wang, Longlong; Wang, Lei; Huang, Jingwei; She, Houde; Wang, Qizhao
Abstract: Construction of heterostructured photocatalysts is a feasible method for improving hydrogen production from water splitting because of its good charge transport efficiency. Herein, we coupled the Ti-MOFs (TiATA) with metal-free graphitic carbon nitride (g-C3 N4 ) to synthesize composites, g-C3 N4 @TiATA, in which a heterostructure was formed between g-C3 N4 and TiATA. The establishment of heterojunctions not only broadens the light absorption range of g-C3 N4 @TiATA (490 nm) by contrast with g-C3 N4 (456 nm), but also greatly accelerates charge migration. Photocatalytic studies present that the construction of heterostructure steering the charges flow from g-C3 N4 to TiATA and then delivery to the cocatalyst of Pt nanoparticles, exhibiting an impressively photocatalytic hydrogen production rate (265.8 μmol·h −1 ) in assistance of 300 W Xenon lamp, which is about 3.4 times as much as g-C3 N4 /Pt. Graphical abstract: We used an applicable synthetic method to prepare a composite by introducing a heterostructure into g-C3 N4 @MOFs and present ameliorated photocatalytic hydrogen production.Image 1 Highlights: TiATA have been incorporated into/onto the sheet-shaped g-C3 N4 and formed a heterostructure. Introduction of a heterostructure into the composites accelerates the electron migration rate. Hydrogen production rate of g-C3 N4 @MOFs/Pt is 265.8 μmol h −1, about 3.4 times as much as g-C3 N4 /Pt.